MO42825-HYDROXYVITAMIN D AND TUBULAR DYSTROPHY IN PATIENTS WITH CKD STAGES 1-3*. (29th May 2021) - Galkina, Olga; Bogdanova, Evdokia; Zubina, Irina; Levykina, Elena; Anpilova, Anastasiia; Sipovski, Vassili; Panina, Iraida; Kovalchuk, Yurii; Smirnov, Alexei
Abstract: Background and Aims: According to a recent data the 25-hydroxyvitamin D (25OHD) level is known to be reduced in advanced stages of CKD presumably due to i) catabolic activity of CYP24 in damaged tubules and ii) increase in renal excretion of 25OHD/Vitamin D binding protein complex. The association of the 25OHD level with different types of tubular damage in early stages (1-3) of CKD is not well investigated. Method: The cross-sectional study included 100 patients (37 male; age 38 (30-50) yrs.) with biopsy proven primary glomerulopathy (membranoproliferative glomerulonephritis (n=9); minimal change disease (n=10); membranous nephropathy (n=11); focal segmental glomerulosclerosis (n=20); IgA nephropathy (n=50)) and CKD stages 1-3 (median eGFR was 64 (33-90) ml/min/1.73 m 2 ). Patients with AKI, infectious diseases, heart failure, respiratory failure and cancer pathology were excluded. The levels of proteinuria, intact parathyroid hormone (PTH) (Beckman Coulter), 25OHD (Abbott) were estimated in all patients. In all cases the following types of tubular damage were analyzed by light microscopy of kidney tissue (hematoxylin and eosin, periodic acid Schiff, Masson's trichrome, Congo red, and Jones' silver) and calculated semi-quantitatively (0 – <10%; 1 – 10-25%; 2 – 26-50% and 3 – >50% of tissue sample): granular dystrophy, hyaline-drop dystrophy, hydropic dystrophy, foamy degeneration and atrophy. The association between clinical and morphological variables was estimated by Spearman's coefficient and multiple linear regression analysis. Results: The patients had a lack or deficiency of 25OHD [Me (Q1-Q3): 13.1 (7.6-19.3) ng/ml]. There was no correlation between serum 25OHD and PTH (r = -0.03, p = 0.86). Proteinuria was negatively associated with level of 25OHD (r = -0.56, p = 0.012). The level of 25OHD was associated with granular (r = -0.39, p <0.05) and hyaline-drop (r = -0.39, p <0.05) tubular dystrophy. In multiple regression analysis the 25OHD level was the independent predictor of the severe hyaline-drop tubular dystrophy (β = -0.33 ± 0.11, p = 0.046) when adjusted for proteinuria (β=0.22±0.11, p=0.062). Conclusion: In patients with CKD stages 1-3 decline in serum 25OHD is associated with the severity of tubular dystrophy. 25OHD level may be useful in laboratory diagnosis as a risk factor of tubular damage in early stages of CKD.